Parents Just Don't Understand: Ambiguity in Stories about the Childhood of Jesus*. (6th January 2016) - Frilingos, Christopher A.
Abstract : The childhood and teenage years, which we think of as crucial to the formation of the adult personality, go all but unnoticed in the canonical accounts of the life of Jesus. Only the Gospel of Luke includes a story about a twelve-year-old Jesus debating with religious experts in the Jerusalem temple and arguing with his parents. Synopses and commentaries sometimes refer to the episode as the "Finding of Jesus in the Temple" (Luke 2:41–52 NRSV), because it begins when his parents lose track of him. Mary and Joseph, having taken Jesus with them on a pilgrimage to Jerusalem for Passover, begin to make the journey back home to Nazareth. Jesus remains in Jerusalem, without his parents' permission: "but his parents did not know it" (καὶ οὐκ ἔγνωσαν οἱ γονε ς [Luke 2:43]). Mary and Joseph search for and find their son "after three days" (2:46), safe and sound, in the great temple of Jerusalem. The boy sits among the elders, asking questions and amazing all with his "understanding" (σύνεσις [2:47]). "Child, why have you done this to us?" Mary reproaches Jesus, "See, your father and I have been worried [ὀδυνώμενοι] looking for you!" (2:48). "Why were you looking for me?" Jesus replies, "Did you not know [οὐκ ᾔδειτε] that I must concern myself with the things of my father?" (2:49). The back and forth confuses the parents: "But they did not understand what he said to them" (καὶ αὐτοὶ οὐ συν καν τὸ ῥ μα ὃ ἐλάλησεν αὐτο ς [Luke 2:50]).